Douching With Water Works Device for Perceived Vaginal Odor With or Without Complaints of Discharge in Women With No Infectious Cause of Vaginitis: A Pilot Study - Ashwin J. Chatwani; Sarmina Hassan; Salma Rahimi; Stacey Jeronis; Vani Dandolu (Hindawi Limited, 2006)
Objective. To determine if douching with Water Works device for 1 month can (1) lower or eliminate perceived vaginal odor by subject; (2) have any effects on vaginal ecosystem. Methods. Ten women with perceived vaginal odor with or without discharge, douched every day for 4 weeks in an open-label, nonrandomized pilot study. Primary outcome measures included perceived vaginal odor by subject, lactobacilli score from Nugent slide, and acceptance of the Water Works douching system. Secondary outcome included the safety of using this douching device. Results. At week 4, there was improvement in vaginal odor (P=.0006) and there was no significant change in lactobacilli score. Conclusion. Douching with Water Works device is associated with reduction or elimination of vaginal odor without adversely affecting the vaginal ecosystem.